Design and Optimization with Genetic Algorithm of Double Rotor Axial Flux Permanent Magnet Synchronous Motor (TORUS Type) for Electrical Vehicles - Akinci, Ruya; Polat, Mehmet (Ieee, 2019)
In recent years, interest in electric vehicles has been increasing. The most important reasons are environmental pollution caused by the density of cars in the settlement centers, the decrease in fossil fuels, the world's shortage of energy resources, advances in efficient and cost-effective electric motor and drive technology, developments in batteries that provide storage of electrical energy and driving safety come to the forefront. One of the most important factors that provide energy efficiency in electric vehicles is the motor. The axial flux permanent magnet synchronous motor, which is a dominant magnet in the field of electrical machinery in recent years, has many advantages over other types of motors. In this study, design equations of axial flux double rotor permanent magnet synchronous motor (TORUS Type) were obtained and optimization of the motor with a genetic algorithm was realized.
4th International Conference on Power Electronics and their Applications (ICPEA) -- SEP 25-27, 2019 -- Elazig, TURKEY
Keywords: genetic algorithm; torus design; axial flux permanent magnet synchronous motor; optimization